PRO VELASCO, M. L. (2021). Introducción a la ética de Robert Spaemann. Granada: Editorial Comares - Conderana Cerrillo, Jesús Manuel (Daimon Revista Internacional de Filosofia, 2023)
Reseña del libro: PRO VELASCO, M. L. (2021). Introducción a la ética de Robert Spaemann. Granada: Editorial Comares.